Information technology in the litigation due to the pandemic COVID-19 - Bakaianova, Nana; Polianskyi, Yurii; Svyda, Oleksii (Cuestiones Políticas, 2020)
Changes in IT information technologies in the judiciary have become particularly evident in the context of the pandemic in an urgent need to file documents electronically, hold online court hearings, and the need to respond and efforts to ensure justice are imposed. In view of this, it is important to analyze the location and importance of information technologies in the judiciary in the face of the COVID-19 pandemic, in order to pay attention to the shortcomings and prospects of their implementation. As a result, the work aims to study the location and importance of information technology in the judiciary in the context of COVID-19. The research methods used are the dialectical, statistical method, method give method, method of a legal analysis document, articles and monographs, generalization method, comparison method, synthesis method, modeling method. By way of conclusion, the scope and significance of information technologies in the judiciary in a pandemic such as this one is highlighted, although their widespread use leads to problems in the courts that require other investigations for effective resolution.